(untitled) (Bangladesh Journal of Botany, 2014)
Five species of the family Rubiaceae belonging to five genera are reported here as new records for Bangladesh. These species are Catunaregam longispina (Link) Tirveng, Galium pusillosetosum Hara, Ophiorrhiza eriantha Wight, Spermacoce exilis (Williams) Adams ex Burger et Taylor and Tarenna stellulata (Hook.f.) Ridl. In Bangladesh, occurrence of the genus Galium L. is also a new record. Each species is presented with updated nomenclature, commonly known synonyms, taxonomic description, ecology, geographical distribution, places of occurrence in Bangladesh, citation of examined specimens and supplementary notes. Illustrations with field photographs of these new records are also provided. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18027 Bangladesh J. Bot. 42(2): 257-264, 2013 (December)